Female Sexual Function after Vaginal Delivery with Episiotomy and Cesarean Section: Fungsi Seksual Perempuan Pascapersalinan Pervaginam dengan Episiotomi dan Seksio Sesarea - I Made W Jembawan; I Made Darmayasa (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To determine the difference of sexual function after vaginal delivery with episiotomy and cesarean section in Sanglah Hospital, Denpasar. Method: This research was conducted using cross sectional method. Sample was collected using consecutive sampling, starting from October 2011-September 2012. Our sample consists of 86 women, 43 post-episiotomy and 43 post-cesarean section. Sexual function was assessed using FSFI (Female Sexual Function Index). Total score was analyzed using independent t-test and difference of sexual function was tested using Chi-square, with significance level p<0.05. Result: Subject characteristics in both groups did not differ significantly. The average time to first sexual intercourse in both groups was 3 months after delivery (p>0.05). There was no significant difference between the two groups in term of sexual arousal and lubrication, with p-value 0.160 and 0.67, respectively. However, we found significant difference in other domains, namely desire (p=0.014), orgasm (p=0.045), satisfaction (p=0.018), pain (p=0.02), and total FSFI score (p=0.006). Sexual dysfunction was found in 18.60% of the episiotomy group and 2.33% of the cesarean section group, with p=0.030. Conclusion: Female sexual dysfunction was found to be significantly different between women post vaginal delivery with episiotomy and women who had cesarean section. Keywords: cesarean section, episiotomy, female sexual function